THE ADOLESCENTS’ CHARACTERISTICS WITH ANEMIA IN SENIOR HIGH SCHOOL MUALLIMAT YOGYAKARTA - Luluk Khusnul Dwihestie; Luluk Rosida (Poltekkes Kemenkes Semarang, 2020)
Anaemia is a global health problem. Anemia many occurs in women and adolescents. This is due to menstruation experienced every month which causes low levels of hemoglobin. Adolescence is a period of growth that requires more nutritional intake. Anemia in adolescent impacts on decreased body immunity and the concentration is reduced. The purpose of this research was to find out the adolescents’ characteristics with anemia in Senior High School Muallimat Yogyakarta. This research is descriptive analytic research with cross sectional approach, a population of 425 of class X students, 40 sample students, purposive sampling technique. The results showed a description of the characteristics of adolescent in Senior High School Muallimat Yogyakarta, showed that the majority of respondents aged 16 years of the 22 respondents (63.0%). The majority of adolescents experienced menarche at age 12 as many as 12 respondents (30.0%). Adolescents having menstrual periods 1 time a month that a majority of 35 respondents (87.5%). In addition, long menstrual majority in the normal category is 3-7 days as many as 29 respondents (72.5%). It is expected that adolescents can consume vegetables and fruits containing iron, as well as Fe tablets during menstruation.